The Whole-Process Low-Voltage Ride-Through Control Strategy for Photovoltaic Power Generation Based on Adaptive Maximum Power Tracking - Yin, Jun (Frontiers in Energy Research, 2022)
The impact of the large-scale disconnection of photovoltaic generators on the grid cannot be ignored, so the low voltage ride-through problem of photovoltaic generators needs to be solved urgently. Especially in the stage after fault recovery, there is a problem that the converter is difficult to switch back to the original control strategy. Therefore, a new control strategy of the whole process low voltage ride through control strategy for photovoltaic power generation based on adaptive maximum Power tracking is proposed. In the initial stage of failure, an adaptive maximum power control strategy is proposed. This control strategy transforms maximum power point tracking (MPPT) control into adaptive maximum power control by feedback of voltage drop amplitude. It can control the output of photovoltaic power quickly and effectively, and realize the zero-voltage crossing of photovoltaic grid-connected system. In the stage after fault recovery, the switching function is established by comparing the network voltage with the rated voltage. The operating state of photovoltaic system can be judged by different output of switching function. It realizes the fast switching of photovoltaic side control strategy during the fault recovery stage. Simulation results show that the proposed method can switch control strategy reliably, and realize the whole process low voltage crossing of photovoltaic power generation quickly.